IMPLEMENTATION OF INCLUSIVE TOURISM PROGRAMS IN GENERAL EDUCATION AND NON-FORMAL INSTSTUTIONS OF UKRAINE - Бейдик, Олександр; Топалова, Олеся (Human Geography Journal, 2015)
The article discusses the relevance of implementing inclusive programs for tourism in general and non-school institutions of Ukraine, due to the creation of inclusive groups in education, tourism, physical culture and sport for self-adaptation, physical, social and psychological rehabilitation of meaningful leisure, participation in tourism activities of children with functional limitations. Particular attention is paid to the problems and prospects of creating a single tourist space for children with disabilities, children, special groups and child health.